2009
DOI: 10.1099/mic.0.028381-0
|View full text |Cite
|
Sign up to set email alerts
|

OmpR positively regulates urease expression to enhance acid survival of Yersinia pseudotuberculosis

Abstract: Yersinia pseudotuberculosis is an enteric bacterium which must overcome the acidic stress in host organs for successful colonization, but how this bacterium survives in acidic conditions remains largely unknown. In the present study, the importance of OmpR in acid survival of Y. pseudotuberculosis YpIII was confirmed by the fact that mutation of ompR (strain ΔompR) greatly reduced cell survival at pH 4.5 or lower. To characterize the regulatory role of OmpR in this acid survival process, proteomic analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 53 publications
1
87
1
Order By: Relevance
“…All these amplified non-coding fragments were cloned into the promoter cloning vector pZT100 [9]. These clones were respectively transformed into YPIII or its derivative strains and the β-galactosidase assay was performed at least in triplicate as previously described [26] at 26°C, or 37°C or 37°C with Ca 2+ depletion.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All these amplified non-coding fragments were cloned into the promoter cloning vector pZT100 [9]. These clones were respectively transformed into YPIII or its derivative strains and the β-galactosidase assay was performed at least in triplicate as previously described [26] at 26°C, or 37°C or 37°C with Ca 2+ depletion.…”
Section: Methodsmentioning
confidence: 99%
“…The gel-retardation was performed as described previously [26]. The LcrF protein was expressed in E. coli BL21(DE3) by pET28a plasmid carrying the lcrF gene from YPIII (named pET28a-LcrF), and purified by Ni-NTA resin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A drop in pH induces the expression of the YPT aspertase ( aspA ) gene; the encoded gene product, AspA, subsequently produces ammonia, allowing the ingested organisms to survive the acidic gastrointestinal environment [125]. Other bacterial factors that promote survival under acidic conditions include urease [126], TatC [127], PhoP, OmpR, and PmrA [128, 129]. Acidic pH also induces a downregulation of the transcriptional regulator, Cra (for catabolite repressor/activator), which increases bacterial acid survival [130].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its role in metabolism, the urease operon is known to be essential for virulence and acid resistance of enteric pathogens, including Y. enterocolitica (54). It has been suggested that the expression of urease genes is regulated by OmpR in Y. pseudotuberculosis (55), but there is no direct evidence for a role of urease in virulence (56). The adiAC genes, encoding arginine decarboxylase and the arginine-agmatine antiporter, respectively, were highly upregulated (fold change, 7.4 and 6.8, respectively; Table S2).…”
Section: Figmentioning
confidence: 99%